Evaluation of a Semi-micro Method for Measuring Platelet Aggregation in Whole Blood Samples - Gordon, John L. (Thrombosis and Haemostasis, 1973)
Platelet aggregation has been measured rapidly and simply in 0.5 ml samples of citrated whole blood, by counting the unaggregated platelets remaining after the samples were mixed with aggregating agents, and the erythrocytes rapidly sedimented by adding physiological saline. Concentration-dependent aggregation responses were obtained with adenosine diphosphate, glass beads, serotonin and connective tissue. Aggregation induced by mixing alone was also measured.The aggregation responses were altered by minor changes in citrate concentration, and increased during the first hour after venepuncture. In heparinised blood samples, platelet counts were reduced and all aggregation responses substantially increased. Extending the time interval between aggregating stimulus and platelet counting had no significant effect on the aggregation responses. The main source of technical error was sampling for platelet counts, and the variablility was inversely related to the size of micropipette used. Results of tests in volunteers established the normal range of responses to aggregating agents, and showed that blood samples taken weeks apart from the same subject gave more variable responses than did samples taken an hour apart.